Exploring race talk and HIV among South African youth. - Mendes, Jacqueline H. (My University, 2011)
This research was an explorative study of the race talk present in discourse when discussing HIV/AIDS and aimed to explore the discourses drawn on by participants during discussions around HIV and AIDS, to explore whether these discourses differed in one-to-one interviews with the author (private talk) compared with those in focus group discussions (public talk) and to investigate how learners navigated race during discussions around HIV/AIDS. The sample was made up of 26 grade 11 learners at a private school in Johannesburg. Data collection was conducted using three focus group discussions (FGD) and several individual one-on-one interviews. Both the interviews and focus groups were conducted using a semi-structured interview guide and recorded on Mp3 players. The data was transcribed using several conversation analysis transcription conventions and later analysed using discourse analysis. An important methodological innovation of this research was its use of HIV/AIDS discussion to capture race discourse. Seven broad themes were analysed and discussed in the research and included (a) HIV/AIDS and the ‘Other’, (b) Race and ‘common sense’, (c) Navigating the perception of racism, (d) Race Trouble and location, (e) Race, Education and Government (f) Race and Apartheid and (g) Public talk Vs. Private talk While this research was mainly exploratory and attempted to investigate as many instances of ‘race talk’ as possible, as well as offer various feasible explanations for the learners’ use of race talk, it was suggested that it may be necessary to explore the possibility of expanding on existing theories to explain the use of race talk among black learners to ‘Other’ people of the same race. Furthermore, while this research did not specifically set out to explore the implications that the intersections between race and HIV/AIDS could have for education, it was suggested that the attachment of apartheid meanings to race (and HIV/AIDS) could lead to learners’ reluctance to critically engage with historical and contemporary texts or avoid discussing issues around HIV/AIDS.
Keywords: Race; HIV/AIDS; South Africa; Discourse